Settlement of Gross Human Rights Violations in the Perspective of Local Wisdom in Indonesia (Case Study of Tanjung Priok) - Hendro Dewanto (Jurnal Dinamika Hukum, 2022)
This article aims to explain the obstacles in handling cases of gross human rights violations in Indonesia and the concept of resolving cases of serious human rights violations in the perspective of local wisdom. This article does not only lead to normative law that is more directed to research on the legal principles but also considers empirical facts as a reality in the settlement of gross human rights violations. Using the Case study of Tanjung Priok, the author focuses on the challenges to the settlement of gross human rights violations in the perspective of local wisdom. The results showed that the settlement of gross human rights violations through the legal process has encountered many challenges and deadlock, along with trauma to victims that result in a severe and long-lasting effect. Second, the settlement of gross human rights violations in the Tanjung Priok case can be carried out by the state, by apologizing to the victim as well as providing reparations, rehabilitation, and compensation as a state responsibility. For the recommendations, the author suggests the need for more detailed arrangements of solutions for victims whose case already has permanent legal force, such as in the Tanjung Priok case, and accommodating the values of local wisdom to improve the norms contained in the Law on Human Rights Court, especially those relating to the process of settling gross human rights violations through non-judicial channels.Keywords: Settlement of Gross Human Rights Violations; Tanjung Priok case; local wisdom